Data for "Identifying Landscape Modification Using Open Data and Tools: The Charcoal Hearths of the Blue Mountain, Pennsylvania". (11th July 2019) - Carter, Benjamin
The data and methods described were used to identify charcoal hearths on the Blue Mountain of eastern Pennsylvania. The data is derived from openly available LiDAR data and was modified using LASTools. This data was used to develop a methodology for the identification of charcoal hearths via a digital elevation model, a hillshade model and a slope analysis. This enabled the identification of 758 potential charcoal hearths. Data and detailed methods description are stored in Open Context and Zenodo. The technique used to produce this data has very high reuse potential since the tools employed are all open source and LiDAR data is often openly available for many states within the US, as well as other countries. An article for the journal, Historical Archaeology, that argues for openness in historical archaeology and utilizes this data has been published recently [1 ].